Analytical Method Development and Validation of Capecitabine from Tablet Dosage Form by Using RP-HPLC - Patil, Rohit A.; Doijad, Dr. Rajendra C.; Lade, Pravin D.; Sankpal, Pournima S. (Asian Journal of Pharmaceutical Research and Development, 2015)
A simple, precise and accurate RP-HPLC method was developed and validated for rapid assay of Capecitabine in tablet dosage form by using a mobile phase consisting mixture of Methanol: Water in the ratio (85:15 % v/v) at the flow rate of 1 mL/min. Symmetry Chromosil C-18 (4.6×250mm), was used as stationary phase. The UV detection wavelength was 303 nm and 10µl sample was injected. The retention time for Capecitabine was 4.2 min. The percentage RSD for precision and accuracy of the method was found to be less than 2%. The method was validated as per the ICH guidelines. The method was successfully applied for routine analysis of Capecitabine in tablet dosage form.